Triflic‐Acid‐Catalyzed Friedel‐Crafts Reaction for the Synthesis of Diaryl Sulfones. Issue 26 (6th July 2022) - Falconnet, Alban; Arndt, Jan‐Dirk; Hashmi, A. Stephen K.; Schaub, Thomas
Abstract: The Friedel‐Crafts sulfonylation for the synthesis of diaryl sulfones derivatives was achieved by using triflic acid (TfOH) as the acidic catalyst with aryl sulfonyl chlorides and arenes at elevated temperatures. Different sulfones could be synthesized with this method in good to excellent yield and with high selectivity. In contrast to the previous methodology reported for this sulfonylation, the catalyst and the excess of arene could be easily recovered and re‐used in further batches. Abstract : The synthesis of diaryl sulfones derivatives through Friedel‐Crafts sulfonylation was achieved by using trifluoromethanesulfonic acid as catalyst with arylsulfonyl chlorides and arenes at elevated temperatures. In this procedure, the catalyst and the surplus of arene may well be retrieved and recycled in further batches.